Legal Protection Against Customers Using Bank Aceh Co-Brand Bank Mandiri Credit Card Products After Bank Aceh Syari'ah Conversion - Muhammad Salda; Muhammad Ridha (Syiah Kuala Law Journal, 2021)
Banking products are inseparable from the existence of an agreement between the Bank and the customer, as stipulated in Article 1338 paragraph (3) of the Civil Code, one of the requirements that must be met in applying the principle of freedom of contract is the good faith of the party making the agreement. Good faith in the implementation stage of the agreement is propriety, where the principle applies equally to both conventional and Sharia banking systems, one of the concrete forms of which is to provide clear information to customers. In this case, it turns out that the Bank Aceh product, namely the Bank Aceh Co-Brand Bank Mandiri credit card, does not provide clear information to customers that the products they use use conventional principles and have a time period. So that the legal problem is how the legal protection for customers who hold Sharia Card. The research was carried out using the empirical juridical research method using a statute approach. The results of the research show that for 3 years according to the time period agreed by the parties in the agreement of the Bank Aceh Co-Brand Credit Card, Bank Mandiri did not explain conversion problems, including ownership of databases, documents and rights, legal ownership of Bank Aceh data also gave to the Bank. Mandiri, as referred to in Article 5 paragraph (5.1.) Number 1 states that, "Bank Aceh is the legal owner of the Bank Aceh customer database provided to Bank Mandiri in connection with the cooperation as stipulated in this Agreement" this should be and is related to changes to the system of conventional to be shari'ah must be informed to the customer.